1996
DOI: 10.1136/adc.74.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics affecting attendance at general outpatient clinics.

Abstract: A study was carried out to identify the characteristics of children who do not attend appointments at general outpatient clinics. Over six months, 359 children who had an appointment at a general clinic were studied using a questionnaire given to parents (740/o response rate) and by inspection of case notes. Based on their first appointment in the study period, children were divided into 'attenders' (n=262) and 'non-attenders' (n=97) for analysis. Nonattenders were significantly more likely to have one or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 7 publications
4
48
3
Order By: Relevance
“…Although no studies have evaluated follow-up http://www.pediatrics.org/cgi/content/full/109/6/e94compliance in similar children, this 28% overall patient noncompliance rate is similar to that reported in studies of well children with general outpatient follow-up appointments. [12][13][14]16 The 22% appointment noncompliance rate with subspecialists in this study also compares to subspecialist appointment noncompliance in other studies. 14,16 Also similar to a previous study, 16 our study found that compliance inversely correlated with the number of follow-up appointments.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although no studies have evaluated follow-up http://www.pediatrics.org/cgi/content/full/109/6/e94compliance in similar children, this 28% overall patient noncompliance rate is similar to that reported in studies of well children with general outpatient follow-up appointments. [12][13][14]16 The 22% appointment noncompliance rate with subspecialists in this study also compares to subspecialist appointment noncompliance in other studies. 14,16 Also similar to a previous study, 16 our study found that compliance inversely correlated with the number of follow-up appointments.…”
Section: Discussionmentioning
confidence: 72%
“…Of the few pediatric follow-up studies reported, all have dealt with well children in outpatient clinics and have shown that these children demonstrate poor compliance with follow-up appointments with nonattendance rates of 16% to 49%. [12][13][14][15][16] Two of these pediatric studies identified factors associated with noncompliance. McClure et al 16 identified 1) older age (78 vs 64 months), 2) caregiver perception of a significantly more severe illness, 3) use of public transportation to reach the clinic, and 4) more appointments scheduled in the previous 12 months in noncompliant patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has reported that paediatric outpatient non-attendance is more likely in lower socioeconomic groups 6 and in families with 'diffuse social problems' . Appointment-related factors are also important: with non-attendance less common in specialist clinics, such as cardiology, longer waiting times increase missed appointments, and non-attenders are more likely to travel by means other than car, have longer journey times, have more appointments per year, or receive their appointment by post rather than in person.…”
Section: Methodsmentioning
confidence: 99%
“…Appointment-related factors are also important: with non-attendance less common in specialist clinics, such as cardiology, longer waiting times increase missed appointments, and non-attenders are more likely to travel by means other than car, have longer journey times, have more appointments per year, or receive their appointment by post rather than in person. 5,6 Non-attendance has been related to parents' perceptions: for example, when they disagree with the need for referral, are fearful of consequences such as unwanted diagnoses, or believe the costs of attending outweigh the benefits. Parental beliefs about children's health seem particularly important, with 'child now well' the most commonly reported reason for non-attendance in one study.…”
Section: Methodsmentioning
confidence: 99%